Key Markers and Epigenetic Modifications of Dental-Derived Mesenchymal Stromal Cells - Jingqiu Chen; Xiaodan Zheng; Nanquan Rao; Yao Huang; Juan Liu; Yanhong Li; Jun Zhang (Stem Cells International)
As a novel research hotspot in tissue regeneration, dental-derived mesenchymal stromal cells (MSCs) are famous for their accessibility, multipotent differentiation ability, and high proliferation. However, cellular heterogeneity is a major obstacle to the clinical application of dental-derived MSCs. Here, we reviewed the heterogeneity of dental-derived MSCs firstly and then discussed the key markers and epigenetic modifications related to the proliferation, differentiation, immunomodulation, and aging of dental-derived MSCs. These messages help to control the composition and function of dental-derived MSCs and thus accelerate the translation of cell therapy into clinical practice.